Lucius Q.C. Lamar, A Compilation of the Laws of the State of Georgia, Passed by the Legislature since the Year 1810 to the Year 1819, Inclusive. Comprising all the Laws Passed within those Periods, Arranged under Appropriate Heads, with Notes of Reference to those Laws, or Parts of Laws, which are Amended or Repealed to which are Added such Concurred and Approved Resolutions, as are Eithier of General, Local, or Private Moment. Concluding with a Copious Index to the Laws, a Separate one to the Resolutions Page 593 (1821) div. 9, § 4 - (:unkn) unknown (General Publisher, 1816)
Prohibited challenging another, or accepting any such challenge, to duel with a sword, pistol, or other deadly weapon. Violators fined a sum of five hundred dollars and imprisoned at hard labour not less than three months nor more than one year.
--
Keywords: DUELING